RANCANG BANGUN APLIKASI PENCARIAN DAN PENAWARAN KERJA BERB ASIS LOKASI (STUDI KASUS: SMKN 5 KABUPATEN TANGERANG) - Naufal Dwizami; Syahriani Syam; Djamaludin Djamaludin (JURNAL ILMIAH FAKULTAS TEKNIK, 2026)
The job search and recruitment process is often hindered by mismatches between job seekers’ and employers’ locations, as well as limited relevant vacancy information. This condition makes recruitment less efficient. This study aims to design and develop an Android-based job search application utilizing Location-Based Services (LBS) with the Haversine Formula to calculate the distance between job seekers and job vacancies. The development method used is Waterfall, starting from requirements analysis, system design, implementation, testing, and maintenance. System testing was carried out using the black-box method to assess functionality and the System Usability Scale (SUS) via questionnaires to measure ease of use. The results show that the application can accurately display job information based on the closest distance, making it easier for job seekers to find jobs according to their location and helping companies reach candidates in targeted areas. Based on SUS testing, the application received a score in the “acceptable” category, indicating its feasibility as a location-based recruitment support solution.